Capital Income Taxation and Economic Growth in Open Economies - Palomba, Geremia (IMF Working Papers; Working Paper ;, 2004)
Do reductions in capital income taxes attract foreign capital and, at the same time, foster economic growth? This paper examines the effect of capital income taxation on the international allocation of capital and on economic growth in a two-country overlapping generations model with endogenous growth and internationally mobile capital. It shows that domestic capital taxes affect both the international allocation of capital and the rate of economic growth and that these two effects are not necessarily the same. A country can increase its share of the existing world capital by changing its taxes but, depending on the elasticity of saving to after-tax returns, this may reduce the rate of capital accumulation and economic growth.